Implementasi Pendekatan Teaching at The Right Level (TaRL) untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VII SMPN 1 Plered - Mutiara, Hana; Hanikah, Hanikah; Sumiri, Sumiri (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
This study aims to examine the improvement of students’ learning outcomes through the implementation of Teaching at The Right Level (TaRL) approach in the topic of Ecology and Biodiversity of Indonesia for Grade VII students at SMPN 1 Plered. The research method used was classroom action research (CAR) involving 22 students from class VII G who received treatment using Teaching at The Right Level (TaRL) approach. The data generated in this study are in the form of observational data on the implementation of students’ activities as well as learning outcome data obtained. The research instrument consisted of multiple-choice test questions. A descriptive quantitative approach was employed to analyze the data by comparing the average post test scores form Cycle I and Cycle II. The results indicated that the implementation of Teaching at The Right Level (TaRL) approach can improve the learning outcomes of Grade VII students at SMPN 1 Plered in the topic of Ecology and Biodiversity of Indonesia. The initial completion rates of 18,2% in the pre-cycle rose to 54,5% in Cycle I and peaked at 72,7% in Cycle II.